167 B-cell-based vaccination elicit potent immunity against glioblastoma. (10th December 2020) - Lee-Chang, Catalina; Miska, Jason; Hou, David; Rashidi, Aida; Zhang, Peng; Burga, Rachel; Horbinski, Crag; Stupp, Roger; Lesniak, Maciej
Abstract : Background: Despite the tremendous effort in basic, translational and clinical research, the standard-of-care of patients with glioblastoma (GBM) has been virtually unchanged for the past two decades, aside from tumor-treating fields. GBM is one of the immunologically 'coldest tumors' where T-cell exclusion is at its maximum, and myeloid infiltration predominates. This is due to profound immunosuppression, the metabolically hostile microenvironment, and the low mutational burden of these tumors. Together, these barriers have hindered the development of effective immunotherapies. With the goal of exploring ways to boost anti-GBM immunity, we developed a B-cell-based vaccine (BVax) that consists of 4-1BBL+ B cells activated with CD40 agonism and IFNgamma stimulation. Methods: Studies on B-cell-driven inflammation have identified a subset of B cells expressing the co-stimulatory marker 4-1BBL (or CD137L) capable of enhancing CD8+ T-cell anti-tumor cytotoxicity. Such activation was achieved through multiple mechanisms, including antigen presentation, T-cell co-stimulation (4-1BBL and CD86), and cytokine production (TNFalpha). Thus, 4-1BBL+ B cells could be utilized to boost anti-tumor CD8+ T-cell response. In order to stabilize their antigen presentation function in-vivo and avoid potential immunosuppressive functions, we activated 4-1BBL+ B cells using CD40 and IFNgamma receptor (IFNgR) ligation (designated as BVax, figure 1 A), both of which were effective to enhance B-cell-mediated antigen presentation (figure 1 B-E). In the present study, we explored the ability of BVax to inhibit GBM growth by promoting tumor-specific CD8+ T-cell immunity and production of tumor-reactive antibodies. BVax's therapeutic effectiveness was examined both alone and in combination with radiation and checkpoint blockade. Results: BVax migrate to key secondary lymphoid organs and are proficient at antigen cross-presentation (figure 2 A), which promotes both the survival and functionality of CD8+ T cells (figure 2 B and C). A combination of radiation, BVax, and PD-L1 blockade conferred tumor eradication in 80% of treated tumor-bearing animals (figure 2 D and E). This treatment elicited immunologic memory that prevented the growth of new tumors upon subsequent re-injection in cured mice (figure 2 D and E). GBM patient-derived BVax were successful in activating autologous CD8+ T cells; these T cells showed a strong ability to kill autologous glioma cells. In addition to the role in activating CD8+ T cells, BVax produce mainly IgGs able to react to tumor cells (figure 4 A) and tumor-associated antigens (figure 4 B). Treatment of glioma bearing-mice with BVax-derived IgG elicited extended animal survival (figure 4 C). Statistical analysis: Data are shown as mean±SD for a continuous variable and number (percentages or optical density measures) for a categorical variable. Differences between two groups were analyzed by Student's t-test. Differences among multiple groups were evaluated using one-way ANOVA with post hoc Tukey's test followed by post hoc Dunn's multiple tests as appropriate. Survival curves were generated via the Kaplan-Meier method and compared by log-rank test and multiple comparisons were adjusted using the Bonferroni method. All the tests are two-sided and p-values or Benjamini-Hochberg adjusted false discovery rates less than 0.05 were considered as significant. Statistical analyses were performed using SAS9.4 and GraphPad Prism7.03. Conclusions: In conclusion, BVax tackles GBM immunosurveillance escape by using both cellular (CD8+ T-cell activation) and humoral (anti-tumor antibody production) immunity. Our study provides an efficient alternative to current immunotherapeutic approaches that can be readily translated to the clinic. Ethics Approval: All human samples (tumor, peripheral blood, and frozen tissue) were collected by the Nervous System Tumor Bank at Northwestern University (NSTB) under the institutional review board (IRB) protocol N° STU00202003. All animal experimentation protocols are approved by the Institutional Animal Care and Use Committee (IACUC) under protocol # IS00002459 at Northwestern University. Acknowledgements: In conclusion, BVax tackles GBM immunosurveillance escape by using both cellular (CD8+ T-cell activation) and humoral (anti-tumor antibody production) immunity. Our study provides an efficient alternative to current immunotherapeutic approaches that can be readily translated to the clinic.